High‐Rate, Durable Sodium‐Ion Battery Cathode Enabled by Carbon‐Coated Micro‐Sized Na3V2(PO4)3 Particles with Interconnected Vertical Nanowalls. Issue 9 (8th February 2016) - Li, Hui; Bi, Xuanxuan; Bai, Ying; Yuan, Yifei; Shahbazian‐Yassar, Reza; Wu, Chuan; Wu, Feng; Lu, Jun; Amine, Khalil
Abstract : Na‐ion batteries have been regarded as promising alternatives for Li‐ion batteries due to the extensive sodium reserves in the world. Na3 V2 (PO4 )3 has been proved to be a good candidate of the cathode materials in Na‐ion batteries but the intrinsic low electrical conductivity and sluggish kinetics handicapped its application. Here, 3D hierarchical Na3 V2 (PO4 )3 particles are synthesized by a facile hydrothermal method, constructed by carbon‐coated 2D Na3 V2 (PO4 )3 nanowalls. Superior cell performance of high rate capability and cycle stability are observed in the well‐defined structure. As the cathode in Na‐ion batteries, it delivers a high capacity almost reaching the theoretical one and exhibits high capacity retention. The enhanced rate capability and cycle performance can be attributed to the improved electrical conductivity from the interconnected carbon layer and the shortened ion diffusion length and high specific surface area from the nanowalls. Abstract : 3D hierarchical Na3 V2 (PO4 )3 particles are synthesized by a facile hydrothermal method, constructed by carbon‐coated 2D Na3 V2 (PO4 )3 nanowalls. When used as cathode of sodium ion batteries, the as‐synthesized material shows excellent electrochemical performances, especially a remarkably improved long‐term cycling stability, which is ascribed to the shortened ion diffusion length and electrical conductivity.